If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.3(x + 20) + -0.02(x + -10) = -2.2 Reorder the terms: 0.3(20 + x) + -0.02(x + -10) = -2.2 (20 * 0.3 + x * 0.3) + -0.02(x + -10) = -2.2 (6 + 0.3x) + -0.02(x + -10) = -2.2 Reorder the terms: 6 + 0.3x + -0.02(-10 + x) = -2.2 6 + 0.3x + (-10 * -0.02 + x * -0.02) = -2.2 6 + 0.3x + (0.2 + -0.02x) = -2.2 Reorder the terms: 6 + 0.2 + 0.3x + -0.02x = -2.2 Combine like terms: 6 + 0.2 = 6.2 6.2 + 0.3x + -0.02x = -2.2 Combine like terms: 0.3x + -0.02x = 0.28x 6.2 + 0.28x = -2.2 Solving 6.2 + 0.28x = -2.2 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6.2' to each side of the equation. 6.2 + -6.2 + 0.28x = -2.2 + -6.2 Combine like terms: 6.2 + -6.2 = 0.0 0.0 + 0.28x = -2.2 + -6.2 0.28x = -2.2 + -6.2 Combine like terms: -2.2 + -6.2 = -8.4 0.28x = -8.4 Divide each side by '0.28'. x = -30 Simplifying x = -30
| 20-k= | | f(x)=ln(8) | | 28x^2=3x+1 | | -(f+5)=-14 | | 10x-y=-23 | | f(x)=-x^2+3x+18 | | 5x-16=14-5y | | 21+x=13 | | 5.3+U=3.20-2.7 | | x+y+3z=13 | | 7n^2+22n+5=0 | | (3x-20)+(7x+30)+(2x+50)=180 | | 3x-8=5x-10 | | y^2+3-(y+1)(y+2)=0 | | 4+3p-1=8p+7-3p | | 1/2d+3=2 | | 6x+12y=77 | | -1.5x+-14.5=-31 | | -2(y-4)=20+2y-12 | | 24.6=29+a(14.51) | | (7/2+2*2)*10= | | 0.7n=-3.5 | | -8(n-5)=2(4n+11) | | 2000+0.05=3600 | | 7x+9+4(x+4)+2= | | 14(t+9)=84 | | -3x-17=-8 | | (x-110)+(3x-10)+(2x)=180 | | 8(7+6b)= | | 2x-125=400 | | 26-2x=2x+3 | | 4(y+7)=5(y-8) |